Supply Chain Integration and Technological Innovation for Business Performance of Aquaculture Contract Farming in Malaysia: A Conceptual Overview - Mohd Azwan Zainol; Zakaria Abas; Ahmad Shabudin Ariffin (International Journal of Supply Chain Management, 2016)
This paper conceptualizes the supply chain integration and technological innovation for business performance of aquaculture contract farming landscape in Malaysia. Based upon the SCM philosophy, it highlights on the three related variables of supply chain integration, namely: external integration with suppliers, external integration with customers and supply chain risks, and technological innovation, and the relation amongst the variables in focus that perhaps could produce possible promising business performance. Hence, ability to conceptualize, observe and give due recognition to the possible relation amongst these variables in question by the prospective aquaculture contract farming participants, perhaps could bring about an insightful engagement for the betterment of the aquaculture business performance.